The Chinese New Year celebration in Malaysia / Ong Sheau Fen - Ong, Sheau Fen (Academy of Language Studies, 2023)
Chinese New Year is also known as Lunar New Year or the Spring Festival. The celebration begins on Chinese New Year's Eve where all family members gather for a reunion dinner. Traditionally, the Chinese New Year lasts for 15 days, from the first day of the first lunar month to the fifteenth. People can visit relatives and friends or go to temples to pray for a safe and auspicious year. Parents or elders will give 'ang pau' to unmarried younger family members. Homes, streets and shopping malls are beautifully decorated. There are other activities that the Malaysian Chinese do to celebrate Chinese New Year, which could not be found in China or other overseas Chinese settlements. These activities include: 1. Malaysia style new year biscuit Malaysia is a multiracial country, and Chinese New Year biscuits are also influenced by other traditions. For example, 'Kuih Kapit', a crispy wafer pastry, is a must-have during the celebration. Initially, it was a traditional biscuit among the Malays and Nyonyas. Later, it was subtly integrated into the Chinese families and became an essential food during the Chinese New Year.